Curators Serving the Public Good - Jean-Paul Martinon (Philosophies, 2021)
This article investigates a principle inscribed at the top of most codes of ethics for curators: they should always “serve the public good.” No self-respecting curator would ever admit to serve “the private good,” that is, the good of the few, whether that of an elite in power or of a circle of friends or allies. The principle of “serving the public good” is inalienable and unquestionable even in situations where it is most open to doubt. However, what exactly is the meaning of this seemingly “true” and on all accounts “universal” principle: “to serve the public good”? To address this question, I look at this principle for the way it is perceived as being both majestic in its impressive widespread acceptance and cloaked in ridicule for being so often disregarded. I will argue—with an example taken from the history of curating—that it is not the meaning attached to the principle that counts, but the respect that it enjoins. I conclude by drawing a few remarks on how the value of the “good” remains, after the principle has been cast aside and the priority of respect is acknowledged, a ghost on the horizon of all curators’ work.